2008
DOI: 10.1177/1359105308093850
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Eating Style between Overweight and Normal-Weight Youngsters

Abstract: Differences in eating styles between overweight and normal-weight youngsters were investigated with a child version of the Dutch Eating Behavior Questionnaire (DEBQ). Subjects were children (n=1458; M: 10.1; SD=1.3) and adolescents (n=1016; M: 14.9; SD=1.5). Overweight adolescent girls scored high on emotional eating while overweight adolescent boys displayed more external eating. In overweight children, already 10.5 per cent displayed emotional eating and 38.4 per cent reported external eating. All overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
174
0
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(223 citation statements)
references
References 38 publications
(72 reference statements)
20
174
0
14
Order By: Relevance
“…Since emotional eating is related to less healthy dietary intake, it has been longitudinally linked to weight gain and obesity, especially in females (102,103) . Although no significant relationship was observed in a small number of studies (104) , other studies identified a significant percentage of emotional eating in overweight children (81,85,105,106) . Braet et al (105) showed that in a large sample of children and adolescents 10·5 % of overweight children reported high scores of emotional eating.…”
Section: Nutrition Research Reviewsmentioning
confidence: 88%
See 1 more Smart Citation
“…Since emotional eating is related to less healthy dietary intake, it has been longitudinally linked to weight gain and obesity, especially in females (102,103) . Although no significant relationship was observed in a small number of studies (104) , other studies identified a significant percentage of emotional eating in overweight children (81,85,105,106) . Braet et al (105) showed that in a large sample of children and adolescents 10·5 % of overweight children reported high scores of emotional eating.…”
Section: Nutrition Research Reviewsmentioning
confidence: 88%
“…Although no significant relationship was observed in a small number of studies (104) , other studies identified a significant percentage of emotional eating in overweight children (81,85,105,106) . Braet et al (105) showed that in a large sample of children and adolescents 10·5 % of overweight children reported high scores of emotional eating. Especially in adolescence, the relationship becomes stronger in overweight females (105) with loss of control (81,106) .…”
Section: Nutrition Research Reviewsmentioning
confidence: 88%
“…In a pilot study, the phrasing of the original DEBQ was slightly adapted, without modifying the content, to enhance the children's comprehension. The different subscales revealed a stable factor structure, satisfying internal consistency (Cronbach's alpha=0.77-0.91) and a good test-retest reliability (r= 0.87-0.90) (Braet et al, 2008;Braet et al, 2007).…”
Section: Emotional Eating Behaviour: Children's Reportmentioning
confidence: 94%
“…The results of studies of an adult cohort of patients with obesity have shown that disorder weight has more associated with restrictive and emotional types of eating behavior [16]. In children group the role of each type of ED in the development of obesity is still discussed and depends largely on belonging to age group [13,14,16].…”
Section: Introductionmentioning
confidence: 99%
“…In children group the role of each type of ED in the development of obesity is still discussed and depends largely on belonging to age group [13,14,16]. The different approaches to meal, choice, volume and nature of food, the time and type of formation of food preferences, the role of parents in different age groups, eating behavior will have features between pre-adolescents and adolescence [6].…”
Section: Introductionmentioning
confidence: 99%